2020
DOI: 10.1093/cid/ciaa1489
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim-sulfamethoxazole Versus Azithromycin for the Treatment of Undifferentiated Febrile Illness in Nepal: A Double-blind, Randomized, Placebo-controlled Trial

Abstract: Background Azithromycin and trimethoprim-sulfamethoxazole (SXT) are widely used to treat undifferentiated febrile illness (UFI). We hypothesized that azithromycin is superior to SXT for UFI treatment, but the drugs are non-inferior to each other for culture-confirmed enteric fever treatment. Methods We conducted a double blind, randomized, placebo-controlled trial of azithromycin (20 mg/kg/day) or SXT (trimethoprim 10 mg/kg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Azithromycin was taken into consideration as the most frequently used prescribed antibiotic, followed by piperacillin/tazobactam. In a similar fashion, several studies undertaken in different healthcare settings in Nepal demonstrated that azithromycin is the most frequently prescribed antibiotic in outpatient departments [ 44 46 ], probably due to its high availability, safety, and affordability. Regarding ceftriaxone and levofloxacin, the significant association of adherence to treatment guidelines was in alignment with previous findings observed in Cape Town Metro District, South Africa [ 34 ].…”
Section: Discussionmentioning
confidence: 91%
“…Azithromycin was taken into consideration as the most frequently used prescribed antibiotic, followed by piperacillin/tazobactam. In a similar fashion, several studies undertaken in different healthcare settings in Nepal demonstrated that azithromycin is the most frequently prescribed antibiotic in outpatient departments [ 44 46 ], probably due to its high availability, safety, and affordability. Regarding ceftriaxone and levofloxacin, the significant association of adherence to treatment guidelines was in alignment with previous findings observed in Cape Town Metro District, South Africa [ 34 ].…”
Section: Discussionmentioning
confidence: 91%
“…Although S Typhi has regained susceptibility to the former first-line drugs (eg, chloramphenicol, ampicillin, and co-trimoxazole) in several countries in south Asia, these options are not as efficacious. 46 , 47 Due to the high prevalence of MDR S Typhi in conjunction with increasing levels of FQNS, patients in sub-Saharan Africa might be unable to obtain or afford effective alternative treatments, such as ceftriaxone or azithromycin. We also highlight the rise of third-generation cephalosporin-resistant S Typhi in south Asia.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Clinical Infectious Diseases, Giri and colleagues report the results of a pragmatic double-blinded, randomized, placebo-controlled trial of azithromycin or trimethoprimsulfamethoxazole (SXT) for empiric treatment of AUFI in Nepal [3]. The trial included 326 patients between 3 and 64 years of age, 163 in each arm, with a fever of 4-14 days' duration from 2 hospitals in Kathmandu randomly assigned to receive either azithromycin (20 mg/kg/ day) or SXT (trimethoprim 10 mg/kg/day plus sulfamethoxazole 50 mg/kg/day) orally for 7 days.…”
mentioning
confidence: 99%